Results of Open Incisional Biopsy and Core Needle Biopsy of Bone Tumors - Syed Bakht Sardar, Abbas Ali, Kamran Saeed, Manqoosh Ur Rehman, Amjad Maqsood, Raza Askari, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The goal of this research was to assess the diagnostic efficacy of open vs percutaneous core needle biopsy (CNB) for musculoskeletal malignancies. Study Design: Retrospective study Place and Duration: This retrospective study was conducted at Department of Orthopaedic, Khyber Teaching Hospital Peshawar during the period from April, 2022 to September, 2022. Methods: There were 96 patients were presented in this study. All patients with a primary bone or soft tissue tumour suspected of being malignant who receive a percutaneous CNB or open biopsy and subsequently develop a tumour were included. Patients were equally divided in two groups. Group I had 48 patients and received open incisional biopsy and group II received core needle biopsy in 48 cases. Fischer’s test was used to compared outcomes among both groups. SPSS 23.0 was used to analyze all data. Results: We found that 28 patients in group I and 30 patients in group II were males. Mean age of the cases in group I was 51.6±7.48 years and in group II mean age was 54.7±10.34 years. As per anatomical distribution, lower extremity was the most common in both groups followed by trunk and upper extremity. In our study favorable outcomes were obtained by CNB in bone sarcoma in terms of diagnostic accuracy, NPV, PPV, sensitivity and specificity as compared to open biopsy but difference was insignificant and in soft tissue sarcoma open biopsy showed a significant good result with p value <0.005. Conclusion: Results from our study showed that the percutaneous biopsy approach was only slightly less effective than open biopsy for soft tissue tumours, whereas the open biopsy technique was more effective for bone tumours. Keywords: Soft tissue sarcoma, Bone sarcoma, Open Biopsy, Core Needle Biopsy